Scaffolding computational thinking: Pre-service teachers learning through Scratch programming - Broza, Orit; Biberman-Shalev, Liat; Chamo, Nurit (Edelweiss Applied Science and Technology, 2025)
This study explores how a technology-rich learning environment, integrating various scaffolding strategies, supports pre-service teachers' (PSTs) development in computational learning using Scratch. A design-based research methodology was applied with 25 second-year PSTs from diverse disciplinary backgrounds. A qualitative research paradigm was used for analysis. The learning environment was intentionally designed to promote autonomy and a sense of responsibility among PSTs through engagement in computational tasks and access to both social and material scaffolds. Social scaffolds included interactions with external individuals, communication with the course lecturer, peer support via a WhatsApp group, and general collegial exchange. Material scaffolds comprised a digital Scratch workbook, recorded class sessions, and system-generated feedback. Findings indicate that these scaffolds significantly contributed to PSTs’ agency and supported the development of independent learner identities. The study concludes that a diverse and flexible digital learning environment, offering multiple modes of support, enhances learners’ ownership of their learning process and autonomy. These insights suggest that incorporating both social and material scaffolding in teacher education programs can effectively foster computational thinking and promote self-directed learning, offering practical guidance for educators designing digitally mediated learning experiences.